Evaluasi Pemberian Tunjangan Penghasilan Pegawai (TPP) Di Lingkungan Dinas Pendidikan Dan Kebudayaan Kabupaten Situbondo - Hosnan, Ahmad; Pramono, Sapto (Soetomo Magister Ilmu Administrasi, 2023)
Efforts to improve employee performance, such as reliable work and responsibility for the tasks assigned so that agency goals can be achieved. One of the drivers of performance is the provision of Employee Income Allowances for Civil Servants which can stimulate enthusiasm and stimulate the performance of the employees themselves, thereby motivating employees to carry out their duties and responsibilities for their work quickly and correctly. This research aims 1) to analyze the evaluation of the provision of employee income allowances (TPP) within the Situbondo Regency Education and Culture Service. 2) to analyze the support and support factors for the provision of employee income allowances (TPP) within the Situbondo Regency Education and Culture Service. The type of research is descriptive qualitative while the data collection techniques are interviews and documentation. The location of the research will be carried out within the Situbondo Regency Education and Culture Service. Data analysis in this research is descriptive qualitative.The research results showed that the provision of TPP to employees was carried out evenly without any analysis of the performance of each existing employee. And also the aim of the TPP itself has not been achieved where the aim of providing the TPP is to motivate employees to work harder and better. In providing TPP based on Situbondo Regent's Regulation Number 14 of 2022 concerning Additional Employee Income for Civil Servants within the Situbondo Regency Government, it has actually been explained that the level of ASN absenteeism and presence greatly influences the provision of TPP as well as the workload of the ASN. The inhibiting factor in giving TPP to employees in the Situbondo Regency Education and Culture Service is that it is carried out without routine supervision of employee performance so that there are still employees who receive TPP even though the employee does not carry out their duties and responsibilities well. The supporting factor is the supporting capacity of the infrastructure and facilities which have been facilitated by the Environment Department of Education and Culture of Situbondo Regency.Keywords: Evaluation, Providing Employee Income Allowances (TPP)